Mineralogical, Textural and Chemical Characteristics of Ophiolitic Chromitite and Platinum Group Minerals from Kabaena Island (Indonesia): Their Petrogenetic Nature and Geodynamic Setting - Idrus, Arifudin (MDPI, 2022)
This contribution presents the first systematic mineralogical study of chromite composition, silicates and PGM (platinum group minerals) by electron microprobes in the podiform chromitite of Kabaena Island (Indonesia) mined in the past. The main target of this study is to understand the petrogenetic nature of the parental melt from which the chromitites of Kabaena Island precipitated and, indirectly, define the geodynamic tectonic setting of their emplacement. The evolution of PGM, from the magmatic stage to low-temperature processes, is also discussed. The variation of the Cr# = Cr/(Cr + Al), being comprised between 0.65 and 0.75, is similar to the podiform-type chromitite and indicates the absence of Al-rich chromitite. The calculated composition of the parental melt varies from arc to MORB (mid-ocean ridge basalts). Several grains of olivine and clinopyroxene have been found in the silicate matrix or included in fresh chromite. Olivine shows a composition typical of a hosted mantle, and clinopyroxene is similar to those analyzed in the forearc of an SSZ (supra-subduction zone). Small PGM, varying in size from 1 to 10 µm, occur in the chromitites. The most abundant PGM is laurite, which has been found included in fresh chromite or in contact with ferrian chromite along the cracks in the chromite. Laurite forms polygonal crystals, and it occurs as a single phase or in association with clinopyroxene and amphibole. Tiny blebs of Ir-Os alloy (less than 2 µm across) have been found associated with grains of awaruite in the serpentine gangue of the chromitites. The composition of the investigated chromitites suggests that they formed in the mantle of a forearc ophiolite. All the discovered grains of laurite are considered to be magmatic in origin, i.e., entrapped as solid phases during the crystallization of chromite at temperatures above 1000◦C and a sulfur fugacity below sulfur saturation. Iridium–osmium alloys are secondary in origin and represent a low-temperature, around 400◦C, exsolution product. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.